Quality Of Apparatus Service Management Regional Water Supply Company North Sumedang Branch Sumedang Regency - Paroli, Paroli (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
This study aims: to find out the service quality of the PDAM apparatus of the Sumedang Utara Subdistrict Branch of the Sumedang District, to find out what factors influence the service quality of the PDAM of the Sumedang Utara Subdistrict of the Sumedang District, to find out how to improve the service quality of the PDAM of the Sumedang Utara Subdistrict of the Sumedang District. The research method used in this research is analytical descriptive. The sampling technique used is purposive sampling. With research informants: Head of Branch, Head of General Section, Head of Public Relations, Head of Production, Employee Implementation. The Data Collection Techniques were carried out, namely the study of literature and field studies consisting of observations, interviews, and documents. While the Data Processing Procedure in this study, namely Data Reduction, Data Display, Data Conclusion Drawing / Verification, and Triangulation. Based on the results of the study concluded that the service quality of the Tirta Medal PDAM North Sumedang Branch of Sumedang Regency: Physical evidence (tangibles), good appearance of the officers / apparatus in serving customers, comfort of the place to perform services. Reliability, the accuracy of officers in serving, has clear service standards. Responsiveness, responding to every customer / applicant who wants to get service, officers / apparatus perform services quickly and accurately. Guarantee (assurance), officers provide timely guarantees in service, guarantee costs in service, guarantee legality in service. Empathy (emphaty), prioritizing the interests of customers / applicants, officers serving with a friendly attitude and courtesy.